2018
DOI: 10.5713/ajas.17.0759
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake, digestibility and energy partitioning in beef cattle fed diets with cassava pulp instead of rice straw

Abstract: ObjectiveThis study was conducted to assess the effects of replacing rice straw with different proportions of cassava pulp on growth performance, feed intake, digestibility, rumen microbial population, energy partitioning and efficiency of metabolizable energy utilization in beef cattle.MethodsEighteen yearling Thai native beef cattle (Bos indicus) with an average initial body weight (BW) of 98.3±12.8 kg were allocated to one of three dietary treatments and fed ad libitum for 149 days in a randomized complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 33 publications
17
38
0
1
Order By: Relevance
“…It would be logical to explain that the content of non-fiber carbohydrates (NFC) in BHM 10 and 20 was lower than BHM 0, and NFC, including starch, sugars and pectin, in which the starch density decreased as the inclusion of BHM in the diet increased; this finding was as expected and it is probably one of the key reasons that affects ADG; although the DMI showed no significant differences which is consistent with the research of Kongphitee et al (2018). Replacing rice straw with an NFC source (cassava pulp) in fermented TMR beef cattle fed diets improved growth performance, energy intake and energy retention because of the increase in digestible feed intake and the digestibility of DM, OM, NDF, and NFC (Kongphitee et al, 2018). The fermented TMR energy density increased as the proportion of cassava pulp in the diet increased due to the fact that cassava pulp has a higher NFC content than rice straw.…”
Section: Discussionsupporting
confidence: 81%
“…It would be logical to explain that the content of non-fiber carbohydrates (NFC) in BHM 10 and 20 was lower than BHM 0, and NFC, including starch, sugars and pectin, in which the starch density decreased as the inclusion of BHM in the diet increased; this finding was as expected and it is probably one of the key reasons that affects ADG; although the DMI showed no significant differences which is consistent with the research of Kongphitee et al (2018). Replacing rice straw with an NFC source (cassava pulp) in fermented TMR beef cattle fed diets improved growth performance, energy intake and energy retention because of the increase in digestible feed intake and the digestibility of DM, OM, NDF, and NFC (Kongphitee et al, 2018). The fermented TMR energy density increased as the proportion of cassava pulp in the diet increased due to the fact that cassava pulp has a higher NFC content than rice straw.…”
Section: Discussionsupporting
confidence: 81%
“…This study demonstrated that an increase in feeding level improves ME intake, ER, and energetic efficiency (Table 4), due to a decrease in the proportion of energy intake to energy excretion in feces, urine, enteric methane, and HP [2,7,9,10, 24]. This result indicated a strong relationship in the ME and DE ratio, which ranged from 0.80 to 0.88; the proportion of ME to DE recommended by the ARC [4], National Research Council (NRC) [5], and Commonwealth Scientific and Industrial Research Organisation (CSIRO) [25] is 0.81, 0.80, and 0.82, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The average of the antilog of the intercept of the linear regression between the log of HP and ME intake was used to estimate the efficiency of ME utilization for maintenance (k m ). Energy retained (ER) was calculated by subtracting the HP from ME intake, and the linear regression of ER on ME intake produced the slope assumed to be the efficiency of energy utilization for growth (k g ) and estimate MEm using ARC [10].…”
Section: Methodsmentioning
confidence: 99%
“…Ensiled total mixed rations have superior storage life [ 1 – 3 ], aerobic stability [ 2 , 4 ], feed intake, and digestibility [ 5 ]. They enhance rumen fermentation characteristics, mitigate enteric methane [ 1 ], and improve growth performance [ 3 , 6 ], and the fatty acid composition of intramuscular fat (marbling) in beef cattle [ 7 ]. However, little research has been conducted to determine the effects of fermented total mixed ration feeding systems on the growth performance and carcass quality of beef cattle commercially fattened on this diet.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it limits productivity and environmental sustainability [ 3 , 8 , 9 ]. Recent reports suggest that increases in the energy content of total mixed rations improve digestibility and growth performance in Brahmans, native Thai breeds, and Zebus crossbred with European beef cattle breeds [ 3 , 6 , 8 ]. For intramuscular fat deposition to occur in finishing cattle, the net energy consumed by the animals must exceed their requirements for maintenance and production.…”
Section: Introductionmentioning
confidence: 99%